Market Orientation, Competitive Advantage and Marketing Performance of Small Medium Enterprises (SMEs) - Astrid Puspaningrum (Journal of Economics, Business, and Accountancy Ventura, 2020)
This study aims to analyze competitive advantage as a variable that mediates the effect of market orientation on marketing performance. This research population is 113,000 SMEs (Small And Medium Enterprises) located in Malang City, which are engaged in food processing, handicrafts, and clothing business units with an observation sample of 100 SMEs. The data analysis technique used in this study is Structural Equation Modeling. The results of this study indicate that SMEs' performance will increase if they can carry out processes and activities related to creating and satisfying customer needs. Besides, market-oriented SMEs contribute to competitive advantage by creating product uniqueness, product quality, and competitive prices, ultimately affecting the performance of SMEs. In order to improve SMEs' performance, efforts must be made to develop marketing strategies, such as paying attention to market orientation, focusing on customer orientation, competitor orientation, and inter-functional coordination, and developing or innovating new products.